Firm types, price-setting strategies, and consumption-tax incidence? - Jarkko Harju; Tuomas Kosonen; Oskar Nordström Skans (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2018)
We analyze price responses to large restaurant VAT rate reductions in two different European countries. Our results show that responses in the short and medium run were clustered around two focal points of zero passthrough and full pass-through. Differences between independent restaurants and chains is the key explanation for this pattern. While nearly all independent restaurants effectively ignored the tax reductions and left consumer prices unchanged, a substantial fraction of restaurants belonging to chains chose a rapid and complete pass-through. In the longer run, prices converged, but primarily through a price reversion among chain restaurants. The stark difference in price responses does not appear to arise because of different market characteristics such as location, initial price levels, meal types or restaurant segment.
Keywords: E31; H22; H32; 330; firm types; VAT incidence; price setting; restaurants